Fracture Resistance of Primary Zirconia Crowns: An In Vitro Study - AlWaleed Abushanan; Rajashekhara B. Sharanesha; Bader Aljuaid; Tariq Alfaifi; Abdullah Aldurayhim (MDPI AG, 2022)
In this study, we evaluated the fracture resistance of three commercially available prefabricated primary zirconia crowns and their correlation with dimensional variance. Methods: a total of 42 zirconia crowns were selected from three companies, (1) NuSmile primary zirconia crowns, (2) Cheng Crowns zirconia, and (3) Sprig EZ crowns. The crowns were divided into two groups based on their location in the oral cavity and further divided into subgroups based on the brand. All of the samples were subjected to fracture tests using a universal testing machine. Results: the mean load observed was highest with Cheng Crowns zirconia anterior crowns (1355 ± 484) and the least load was seen with Sprig EZ anterior crowns with a mean load of 339 ± 94. The mean load observed was highest with Cheng Crowns zirconia posterior crowns (1990 ± 485) followed by NuSmile posterior crowns and the least load was seen with Sprig EZ posterior crowns with a mean load of 661 ± 184. Conclusion: the Cheng crowns showed the highest fracture resistance amongst all three groups. Overall, the zirconia crowns (anterior and posterior) tested showed optimum mechanical properties to withstand the masticatory forces.